PATH-10. A CASE OF ADULT THALAMIC DIFFUSE MIDLINE GLIOMA, H3 K27-ALTERED WITH AN IMPRESSIVE RESPONSE TO RADIOTHERAPY AND CONCOMITANT PLUS ADJUVANT TEMOZOLOMIDE. (14th November 2022) - Rousseau, Julien; Labidi, Moujahed; Bahary, Jean-Paul; Bélanger, Karl; Berthelet, France; Lapointe, Sarah
Abstract: Diffuse midline glioma (DMG), H3 K27-altered is a newly defined diagnosis in the 2021 WHO Classification of Tumors of the Central Nervous System. H3 K27 alterations are associated with a uniformly poor prognosis in children with DMG, but they have been linked to improved survival in adults. Clinical experience in adults with DMG, H3 K27M-altered remains limited. Consequently, there exists a knowledge gap regarding the optimal management and responsiveness to chemoradiation therapy, which translates into the current absence of standard treatment. Here we present the case of an 18-year-old female patient treated for a thalamic DMG, H3 K27-altered at a Canadian tertiary center. The patient first presented with headache, dysarthria, and signs of increased intracranial pressure. Her initial brain magnetic resonance imaging demonstrated a right thalamo-mesencephalic lesion with central nodular enhancement and secondary hydrocephalus. She underwent an endoscopic third ventriculostomy followed by a subtotal resection, and pathology confirmed the presence of a DMG, H3 K27-altered, WHO grade 4. She was treated with combined radiotherapy and concomitant plus adjuvant (12 cycles) temozolomide. The Stupp regimen induced a spectacular response with a reduction in tumor dimensions on T2/FLAIR (20 x 18 mm versus 60 x 51 mm), > 50% decrease in size of the enhancing component, complete resolution of mass effect, and return to functional independence (KPS = 100%). Unfortunately, her disease progressed 16 months after diagnosis and she passed away 8 months later, despite having received 3 cycles of ONC201 through a clinical trial. Her progression-free survival (16 months) was superior to that reported in the literature, which could be related to her young age, subtotal resection status, and thalamic location. Although the addition of chemotherapy to adjuvant radiotherapy has not been shown to improve survival in children with DMG, the Stupp regimen may provide a survival benefit in adults.